2019
DOI: 10.1111/all.13762
|View full text |Cite
|
Sign up to set email alerts
|

Dietary coconut oil ameliorates skin contact hypersensitivity through mead acid production in mice

Abstract: Coconut oil is used as a dietary oil worldwide, and its healthy effects are recognized by the fact that coconut oil is easy to digest, helps in weight management, increases healthy cholesterol, and provides instant energy. Although topical application of coconut oil is known to reduce skin infection and inflammation, whether dietary coconut oil has any role in decreasing skin inflammation is unknown. In this study, we showed the impact of dietary coconut oil in allergic skin inflammation by using a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 75 publications
3
16
0
Order By: Relevance
“…These discrepancies may arise from various factor, for example, the type of dietary oil used in the experiment. As shown before, different dietary fats have distinct effects on the immune response, including CHS reaction 34 . Here, we show that DIO exacerbates CHS response to DNFB in Rag1 −/− mice.…”
Section: Discussionsupporting
confidence: 81%
“…These discrepancies may arise from various factor, for example, the type of dietary oil used in the experiment. As shown before, different dietary fats have distinct effects on the immune response, including CHS reaction 34 . Here, we show that DIO exacerbates CHS response to DNFB in Rag1 −/− mice.…”
Section: Discussionsupporting
confidence: 81%
“…The 18-HEPE is further transformed to resolvin E1 by 5-LOX expressed on neutrophils [42,43]. We also recently showed that neutrophil 5-LOX contributes to the production of leukotriene B 4 from ARA and influences the development of inflammation [26].…”
Section: Discussionmentioning
confidence: 95%
“…Neutrophils were collected from bone marrow cells of female C57BL/6J mice as previously reported [26]. Bone marrow cells were suspended in RPMI 1640 medium containing 2% NCS and carefully added onto 62% Percoll (GE Healthcare, Chicago, IL, USA) in RPMI 1640 medium.…”
Section: Culture Of Bone Marrow-derived Neutrophils and Eosinophilsmentioning
confidence: 99%
“…In addition to 17,18‐EpETE and 12‐HEPE, several other lipid mediators have been identified that inhibit CHS by targeting different cells. For example, oleic acid‐derived mead acid acts directly on neutrophils to inhibit their migration and leukotriene B 4 production, 41 and EPA‐derived RvE1, which is a metabolite of 18‐HEPE, impairs the mobility of cutaneous dendritic cells by blocking leukotriene B 4 ‐leukotriene B 4 receptor 1 signaling, thereby reducing skin inflammation in CHS 39 . However, although 18‐HEPE is a substrate of functional EPA‐derived metabolites of RvEs, we found here that 18‐HEPE had little effect on ear swelling, suggesting that 18‐HEPE is not metabolized to RvEs.…”
Section: Discussionmentioning
confidence: 99%